Spinodally Decomposed PbSe-PbTe Nanoparticles for High-Performance Thermoelectrics: Enhanced Phonon Scattering and Unusual Transport Behavior - Kim, Min-Seok; Lee, Woo-Jin; Cho, Ki-Hyun; Ahn, Jae-Pyoung; Sung, Yun-Mo (AMER CHEMICAL SOC, 2016)
Dramatic enhancements in the figure of merit have been obtained in bulk thermoelectric materials by doping, band engineering, and nanostructuring. Especially, in p-type thermoelectrics, high figure of merits near 2.0 have been reported in a few papers through the reduction in lattice thermal conductivity and the advancement in power factors. However, there exists no report on the n-type systems showing high figure of merits because of their intrinsically low Seebeck coefficients. Here, we demonstrate that a nanostructured bulk n-type thermoelectric material that was assembled by sintering spinodally decomposed lead chalcogenide nanoparticles having a composition of PbSe0.5Te0.5 reaches a high figure of merit of 1.85. The spinodally decomposed nanoparticles permit our thermoelectric material to have extremely low lattice thermal conductivity and a high power factor as a result of nanostructuring, electronic optimization, insertion of an impurity phase and phase change in local areas. We propose that this interesting concept would be one of the promising approaches that overcome limitation arising from the fact that most parameters in the figure of merit are closely correlated.
Keywords: THERMAL-CONDUCTIVITY; PHASE-SEPARATION; FIGURE; MERIT; CONVERGENCE; TEMPERATURE; EFFICIENCY; DISTORTION; GROWTH; ALLOY